Research on the Application Status and Improvement of Modern Technology of Electronic Information Engineering. Issue 2 (April 2021) - Ye, Jingjing
Abstract: The in-depth application of modern technology in modern electronic information engineering has greatly changed people's lives and work, and its convenience is very strong. However, it can also be seen from practical applications that there are still some problems that have not been resolved. This article summarizes the application status of modern electronic information engineering technology based on previous work experience. The author discusses how to improve the modern technology of electronic information engineering from five aspects: how to create a good market order, how to optimize the development environment, how to strengthen the modern innovation level of electronic information engineering, how to train professional and technical personnel, and how to increase support.